Theology in Intercultural Design - Ozankom, Claude. (Intercultural Theology and Study of Religions, 2010)
Among the consequences of the all engulfing process of globalisation is the experience that not only it promotes interdependence among peoples, folks, cultures and religions, but it also creates problems and tensions. The assignment of a thoughtful and practice-oriented accompanying of this development poses itself subsequently. From this background different lectures are being conducted in different places; research initiatives as well as projects are started and executed while several publications are featuring. Visible here is the fact that although there abound rich reservoirs of knowledge, there is still no clarity as to the contents and the theoretical and methodical contrasts that are yet to be examined. Zu den Folgen des um sich greifenden Globalisierungsprozesses, zählt die Erfahrung, dass er nicht nur die Interpendenz unter Menschen, Völkern, Kulturen und Religionen vorantreibt, sondern auch Probleme und Spannungen auslöst. Diese Situation ist denkerisch und praxisorientiert aufzuschließen. Es wurden an verschiedenen Standorten Lehrveranstaltungen durchgeführt, Forschungsprojekte in Angriff genommen und Publikationen vorgelegt. Auffällig hierbei ist: Obwohl der erreichte Wissensstand bereits reichhaltig ist, besteht keine Klarheit hinsichtlich der zu untersuchenden Inhalte und der theoretischen und methodischen Gegensätze.